ACCELERATED DEPRECIATION AND THE ALLOCATION OF INCOME TAXES. - Davidson, Sidney (The Accounting Review, 1958)
Many firms use an accelerated depreciation method for calculating the depreciation deduction to be made on the income tax return, but employ the straight-line depreciation method for calculating the depreciation expense figure for financial statements. In considering the effect of this action on income tax expense and income tax liability, attention must be centered on the taxpaying entity, the firm as a whole. For a static or growing firm, current tax savings from this source will not adversely affect income tax charges of future years. In fact, the growing firm can look forward to an ever-increasing annual tax saving continuing year after year. Only a moribund firm with declining investment in capital assets is likely to be faced by a substantial deferred tax liability, and then only if its dying years are profitable ones. Although the analysis indicates that a liability for future taxes from this source should be recognized only in rare cases, disclosure of any difference between the amount of depreciation claimed on the tax return and that shown in the income statement is a desirable reporting practice and should be employed regularly.